2016
DOI: 10.21037/atm.2016.09.34
|View full text |Cite
|
Sign up to set email alerts
|

A rare presentation of acute heart failure secondary to aggressive uterine leiomyosarcoma metastatic to the myocardium initially diagnosed as hypertrophic obstructive cardiomyopathy

Abstract: Uterine sarcoma is the cause of 3-9% of all uterine malignant neoplasms and has a 2-fold higher incidence in black women as compared to white women. Cellular atypia and abundant mitoses (≥10 per 10 high power fields) as seen in this patient are associated with an increased risk for metastases. Metastases to the heart are infrequently reported with a handful of cases in the literature. We present a case of a 51-year-old woman with aggressively metastatic uterine leiomyosarcoma causing acute heart failure 4 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“… 10 , 11 Four cases were diagnosed by echocardiography, and congestive heart failure was the most common presentation. 3 , 5 , 12 Prior case reports demonstrated that metastatic deposits can be found in various cardiac chambers and valves, but none reported pericardial metastatic involvement by leiomyosarcoma: three cases reported metastatic deposits in the left atrium, 3 , 5 , 6 two involving the right atrium, 7 , 8 two with right ventricular involvement, 11 , 13 two cases demonstrated left ventricular involvement, 12 , 14 and one report each demonstrating mitral 15 and tricuspid valve 9 involvement, respectively. In general, tumors may spread to the heart and pericardium by one of four pathways: (1) retrograde lymphatic extension, (2) hematogenous spread, (3) direct contiguous extension, and (4) transvenous extension.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Four cases were diagnosed by echocardiography, and congestive heart failure was the most common presentation. 3 , 5 , 12 Prior case reports demonstrated that metastatic deposits can be found in various cardiac chambers and valves, but none reported pericardial metastatic involvement by leiomyosarcoma: three cases reported metastatic deposits in the left atrium, 3 , 5 , 6 two involving the right atrium, 7 , 8 two with right ventricular involvement, 11 , 13 two cases demonstrated left ventricular involvement, 12 , 14 and one report each demonstrating mitral 15 and tricuspid valve 9 involvement, respectively. In general, tumors may spread to the heart and pericardium by one of four pathways: (1) retrograde lymphatic extension, (2) hematogenous spread, (3) direct contiguous extension, and (4) transvenous extension.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine leiomyosarcomas are rare with an incidence of 0.36 per 100,000 woman-years in the USA, accounting for 3–9% of all uterine malignant neoplasms. [ 1 ] Cardiac metastases from uterine leiomyosarcoma have been infrequently reported with only a handful of cases in literature. [ 1 ] This unique pathology behaves in an unpredictable fashion from the disease progression to presenting symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Cardiac metastases from uterine leiomyosarcoma have been infrequently reported with only a handful of cases in literature. [ 1 ] This unique pathology behaves in an unpredictable fashion from the disease progression to presenting symptomatology. [ 2 ] In our patient, her cardiac symptoms preceded uterine symptoms, as she was unaware of the primary endometrial leiomyosarcoma lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations